Repair of Y-T Humeral Condyle Fractures with Locking Compression Plate Fixation - Moffatt, Felicity; Kulendra, Elvin; Meeson, Richard L. (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objectives The aim of this study was to describe the use of locking compression plates (LCP) in Y-T humeral condyle fractures and to evaluate their clinical outcome.Methods This study involved a retrospective review, including clinical, radiographical and canine brief pain inventory outcome evaluation.Results Eighteen consecutive dogs met the inclusion criteria, and 15/18 were considered to have humeral intracondylar fissure. Twelve of 18 dogs had simple fractures, and the remaining six had comminuted fractures. Postoperative radiographs revealed accurate intracondylar reconstruction (articular step defect [ASD] < 1 mm) in 17/18 of patients. Short-term outcome was considered fully functional in 9/13 and acceptable in 3/13 patients. Complications were diagnosed in 2/13; infection in one with resolution after antibiotic treatment, and one case of implant failure. Nine of 18 owners provided postoperative questionnaire responses (median 25; range: 14–52 months) and 8/9 clients perceived the treatment to have resulted in an excellent overall outcome.Clinical significance Repair of Y-T humeral fractures with LCP allowed for hybrid fixation and monocortical screw placement in distal fracture fragments. There was no significant ASD at the intracondylar fracture line in most cases. ASD using combined medial and lateral approaches depends upon the accuracy of supracondylar reduction, particularly on the side that is reduced and stabilized first, and the use of locking screws may have been influential in minimizing primary loss of reduction, potentially maintaining the initial fragment reduction.
Keywords: locking compression plate; humeral; condylar fracture; Y fracture; fracture fixation; dogs